Long‐range crystal‐lattice distortion fields of epitaxial Ge–Sb–Te phase‐change materials. Issue 4 (16th December 2013) - Katmis, Ferhat; Schmidbauer, Martin; Bokoch, Sergiy M.; Rodenbach, Peter; Riechert, Henning; Calarco, Raffaella
<x xml:space="preserve">Abstract</x> The structural evolution of Ge–Sb–Te‐based phase‐change material during molecular beam epitaxy growth is investigated. The in situ and ex situ synchrotron‐based X‐ray scattering results reveal the formation and evolution of defects‐induced inhomogeneities during growth. The scattered intensity in the vicinity of various Bragg reflections indicates a specific scattering vector‐dependent anisotropy in the diffuse scattering regime. The average local static distortion fields of the defects‐induced inhomogeneities are estimated to be in between 2.5 and 3.0 nm. The defects‐induced diffuse scattering anisotropy, observed for the particular Bragg points, arises from the combination of the elastic and crystalline anisotropies that are caused by the large number of vacancies. The experiments show that the large‐size defect clusters create inhomogeneity‐driven tetragonal fields inserted into the metastable phase of the Ge–Sb–Te host crystal.